Effect of Bone Protein addition to the system: Calcium Titanate - Farhan, Fadhil K.; Mawat, Mazin Mohammed; Odah, Jafer Fahdel (Physics and Chemistry of Solid State, 2024)
A ceramic compound was prepared by mixing calcium carbonate in a mole ratio to nanoscale titanium dioxide powder using the method of manufacturing powders, in addition to mixing and grinding for long hours up to 72 hours in the presence of non-ionic water. After which the powder was extracted and then it was dried at a temperature of 100 oC for 4 hours, and then it was treated at 800 oC in a convection oven at 10 oC of heat for every 2 minutes. An X-ray diffraction test of the ceramic powder was performed before adding the synthesized bone protein that was prepared from cow bones. Scanning electron microscopy and energy dispersion spectrometry were also performed before and after adding the BMP. The results of the examination showed a big difference in the properties of the compound in terms of the atomic structure, as new compounds of bone components were introduced into the atomic structure, and the results were interpreted through the practical intensity of examining the body fluid-like solution (SBF).